2017
DOI: 10.1093/sleep/zsx205
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Influences Day-to-Day Variability in Sleep in Drosophila melanogaster

Abstract: Patterns of sleep often vary among individuals. But sleep and activity may also vary within an individual, fluctuating in pattern across time. One possibility is that these daily fluctuations in sleep are caused by the underlying genotype of the individual. However, differences attributable to genetic causes are difficult to distinguish from environmental factors in outbred populations such as humans. We therefore employed Drosophila as a model of intra-individual variability in sleep using previously collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 94 publications
1
16
0
Order By: Relevance
“…However, when we examined daily fluctuations in sleep using the standard deviation of each sleep trait (σ) to represent intra-individual differences ( Knutson et al 2007 ; Mezick et al 2009 ; Buman et al 2011 ; Angulo-Barroso et al 2013 ; Dillon et al 2014 ), we found that night and 24-hour sleep σ and night bout number σ were increased in lines derived from short-sleeping populations, and reduced in lines derived from the long-sleeping populations ( P = 0.0398, 0.0428, and 0.0312, respectively, 3-way ANOVA) (Tables S1, S7, and S8). Short sleepers, therefore, have more daily fluctuations in sleep than long sleepers, and their sleep also tends to differ from individual to individual ( Harbison et al 2013 ; Wu et al 2018 ). We speculate that the short sleepers may have greater sensitivity to small environmental fluctuations, and that this may result in more variable sleep.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when we examined daily fluctuations in sleep using the standard deviation of each sleep trait (σ) to represent intra-individual differences ( Knutson et al 2007 ; Mezick et al 2009 ; Buman et al 2011 ; Angulo-Barroso et al 2013 ; Dillon et al 2014 ), we found that night and 24-hour sleep σ and night bout number σ were increased in lines derived from short-sleeping populations, and reduced in lines derived from the long-sleeping populations ( P = 0.0398, 0.0428, and 0.0312, respectively, 3-way ANOVA) (Tables S1, S7, and S8). Short sleepers, therefore, have more daily fluctuations in sleep than long sleepers, and their sleep also tends to differ from individual to individual ( Harbison et al 2013 ; Wu et al 2018 ). We speculate that the short sleepers may have greater sensitivity to small environmental fluctuations, and that this may result in more variable sleep.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic studies of wild-derived populations of flies have identified thousands of polymorphisms that affect morphological, physiological, and behavioral complex traits ( Ayroles et al 2009 ; Jordan et al 2012 ; Mackay et al 2012 ; Weber et al 2012 ; Chow et al 2013 ; Harbison et al 2013 ; Ellis et al 2014 ; Vaisnav et al 2014 ; Arya et al 2015 ; Ayroles et al 2015 ; Dembeck et al 2015a ; Dembeck et al 2015b ; Gaertner et al 2015 ; Garlapow et al 2015 ; Ivanov et al 2015 ; Montgomery et al 2015 ; Morgante et al 2015 ; Morozova et al 2015 ; Shorter et al 2015 ; Unckless et al 2015 ; Zwarts et al 2015 ; Chow et al 2016 ; He et al 2016 ; Hunter et al 2016 ; Vonesch et al 2016 ; Harbison et al 2017 ; Lobell et al 2017 ; Wu et al 2018 ). A challenging next step is to demonstrate how the polymorphisms associated with a trait influence phenotype ( Mackay et al 2009 ; Albert and Kruglyak 2015 ).…”
mentioning
confidence: 99%
“…Sleep is regulated by complex genetic architecture and is highly influenced by genetic variation (Cirelli, ; Wu, Kumar, Serrano Negron, & Harbison, ). While many genes have been identified using mutagenesis approaches, much less is known about the modulation of sleep via naturally occurring genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant correlation between starvation resistance and (g) triglyceride and (h) glycogen levels, while there is no correlation between starvation resistance and (i) free glucose levels. For measurements of nutrient stores for all localities, see Appendix S4 Sleep is regulated by complex genetic architecture and is highly influenced by genetic variation (Cirelli, 2009;Wu, Kumar, Serrano Negron, & Harbison, 2017). While many genes have been identified using mutagenesis approaches, much less is known about the modulation of sleep via naturally occurring genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Although fly GWAS retain most of the advantages and disadvantages already discussed for human and rodent GWAS, they alleviate some problems by reducing environmental confounds and permitting quantification of phenotypic variability between individuals. Vast numbers of isogenic flies allow effective mapping of this variability to the genome, unlike in humans, where isogenic sample size is limited to sets of twins [209,210]. Further, linkage disequilibrium diminishes rapidly in flies compared to mammals, increasing the chances that SNPs associated with AUDs represent causal, rather than merely linked, variants [129,211].…”
Section: Fly Gwas and Qtl Analysesmentioning
confidence: 99%